Failure Analysis on Water Heater Tube - Sufian Hardi Bin Yusof, Sufian Hardi (2008)
The main purpose of this project is to study and identify what elements that causes the corrosion of the water tube heater and to be able to analyze the results of experiments done on the corroded water tube heater. At the end of this project, we can identify the real cause of the failure of this tube heater.